Microbial phenazine production enhances electron transfer in biofuel cells - Rabaey, Korneel; Boon, Nico; Höfte, Monica; Verstraete, Willy (Environmental science & technology, 2005)
High-rate electron transfer toward an anode in microbial fuel cells (MFCs) has thus far not been described for bacteria-producing soluble redox mediators. To studythe mechanism of electron transfer, we used a MFC isolate, Pseudomonas aeruginosa strain KRP1. Bacterial electron transfer toward the MFC anode was enabled through pyocyanin and phenazine-1-carboxamide. The presence of the anode stimulated pyocyanin production. Mutant strains, deficient in the synthesis of pyocyanin and phenazine-1-carboxamide, were unable to achieve substantial electron transfer and reached only 5% of the wild type's power output. Upon pyocyanin addition, the power output was restored to 50%. Pyocyanin was not only used by P. aeruginosa to improve electron transfer but as well enhanced electron transfer by other bacterial species. The finding that one bacterium can produce electron shuttles, which can be used also by other bacteria, to enhance electron-transfer rate and growth, has not been shown before. These findings have considerable implications with respect to the power output attainable in MFCs.